Associations Between Emotional Intelligence, Socio-Emotional Adjustment, and Academic Achievement in Childhood: The Influence of Age. (June 2014) - Brouzos, Andreas; Misailidi, Plousia; Hadjimattheou, Anastasia
This study examined the relationship between trait emotional intelligence (EI) with children's socio-emotional adjustment at school and academic achievement. Children aged 8 to 10 ( n = 106) and 11 to 13 years ( n = 99) completed the youth version of the Emotional Quotient Inventory (EQ-i: YV). Their socio-emotional adjustment was measured with scales from the Teacher's Report Form assessing socio-emotional problems and adaptive functioning at school. Trait EI was positively correlated with aspects of children's adaptive functioning and academic achievement only in the 11- to 13-year-old but not in the 8- to 10-year-old group. Our results illustrate the importance of taking age into consideration when assessing the relationship between trait EI with socio-emotional adjustment at school and academic achievement. The consequences and limitations of these findings are discussed.